Musclin prevents depression-like behavior in male mice by activating urocortin 2 signaling in the hypothalamus - Ataka, Koji; Asakawa, Akihiro; Iwai, Haruki; Kato, Ikuo (Frontiers in Endocrinology, 2023)
Introduction Physical activity is recommended as an alternative treatment for depression. Myokines, which are secreted from skeletal muscles during physical activity, play an important role in the skeletal muscle-brain axis. Musclin, a newly discovered myokine, exerts physical endurance, however, the effects of musclin on emotional behaviors, such as depression, have not been evaluated. This study aimed to access the anti-depressive effect of musclin and clarify the connection between depression-like behavior and hypothalamic neuropeptides in mice. Methods We measured the immobility time in the forced swim (FS) test, the time spent in open arm in the elevated-plus maze (EPM) test, the mRNA levels of hypothalamic neuropeptides, and enumerated the c-Fos-positive cells in the paraventricular nucleus (PVN), arcuate nucleus (ARC), and nucleus tractus solitarii (NTS) in mice with the intraperitoneal (i.p.) administration of musclin. Next, we evaluated the effects of a selective corticotropin-releasing factor (CRF) type 1 receptor antagonist, selective CRF type 2 receptor antagonist, melanocortin receptor (MCR) agonist, and selective melanocortin 4 receptor (MC4R) agonist on changes in behaviors induced by musclin. Finally we evaluated the antidepressant effect of musclin using mice exposed to repeated water immersion (WI) stress. Results We found that the i.p. and i.c.v. administration of musclin decreased the immobility time and relative time in the open arms (open %) in mice and increased urocortin 2 (Ucn 2) levels but decreased proopiomelanocortin levels in the hypothalamus. The numbers of c-Fos-positive cells were increased in the PVN and NTS but decreased in the ARC of mice with i.p. administration of musclin. The c-Fos-positive cells in the PVN were also found to be Ucn 2-positive. The antidepressant and anxiogenic effects of musclin were blocked by central administration of a CRF type 2 receptor antagonist and a melanocortin 4 receptor agonist, respectively. Peripheral administration of musclin also prevented depression-like behavior and the decrease in levels of hypothalamic Ucn 2 induced by repeated WI stress. Discussion These data identify the antidepressant effects of musclin through the activation of central Ucn 2 signaling and suggest that musclin and Ucn 2 can be new therapeutic targets and endogenous peptides mediating the muscle−brain axis.